2002
DOI: 10.1104/pp.010811
|View full text |Cite
|
Sign up to set email alerts
|

The Negatively Acting Factors EID1 and SPA1 Have Distinct Functions in Phytochrome A-Specific Light Signaling

Abstract: EID1 (empfindlicher im dunkelroten Licht) and SPA1 (suppressor of phytochrome A[phyA]-105) function as negatively acting components in phyA-specific light signaling. Mutants in the respective genes led to very similar phenotypes under weak-light conditions. To examine whether both genes are functionally redundant, detailed physiological and genetic analyses were performed with eid1 and spa1 mutants isolated from the same wild-type background. Measurements of hypocotyl elongation, anthocyanin accumulation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…The phenotypic effects of spa1 mutations are dependent on a functional PHYA gene, suggesting that SPA1 is important for normal phyA signaling (Hoecker et al, 1998). Moreover, spa1 mutations enhance both modes of phyA action, the response to FRc and the very low fluence response (Baumgardt et al, 2002;Zhou et al, 2002). It was also suggested that growth promotion by SPA1 counteracts phytochromemediated growth inhibition in hypocotyls (Parks et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic effects of spa1 mutations are dependent on a functional PHYA gene, suggesting that SPA1 is important for normal phyA signaling (Hoecker et al, 1998). Moreover, spa1 mutations enhance both modes of phyA action, the response to FRc and the very low fluence response (Baumgardt et al, 2002;Zhou et al, 2002). It was also suggested that growth promotion by SPA1 counteracts phytochromemediated growth inhibition in hypocotyls (Parks et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several of our observations clearly indicate that the mutation in the HA subdomain has very severe influences on light signal transduction events related to EID1, which functions as an important negative regulator in phyA-dependent HIR signaling (Bü che et al, 2000;Dieterle et al, 2001;Zhou et al, 2002;Marrocco et al, 2006). First, the phyA-402 mutation robustly suppresses the effects of the strong allele eid1-3 under continuous far-red and weak red light, even though it does not severely affect light sensitivity in the wild type under the same light conditions (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The phyA-402 Mutation Causes a Shift in Spectral Sensitivity and Persistence of HIR Because EID1 functions as an important negative regulator in far-red HIR (Bü che et al, 2000;Dieterle et al, 2001, Zhou et al, 2002Marrocco et al, 2006), it was quite astonishing that the wild type and phyA-402 exhibited nearly identical fluence rate dependencies for inhibition of hypocotyl elongation and for anthocyanin accumulation. To search for more subtle influences of phyA-402 on far-red HIR, additional fluence rate response curves were measured for seedlings irradiated with narrow-banded interference filters in order to construct an action spectrum for hypocotyl elongation (Supplemental Fig.…”
Section: Physiological Characterization Of Phya-402mentioning
confidence: 99%
See 2 more Smart Citations